TEKNOLOGI ORGANISASI HMI CABANG DENPASAR: PERSAMAAN DAN PERBEDAAN DENGAN HMI CABANG PULAU JAWA - Handika Alfirdaussy, Fanny Dwi; Nugroho, Wahyu Budi; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 1 No 2 (2019), 2020)
ABSTRACT This study analyzes and describes the use and developments of technology that occur with the Himpunan Mahasiswa Islam (HMI) organization in Denpasar. Besides, this research also discussion about similarities and differences in the organizational technology of the HMI Denpasar Subdivision and the HMI Java Island Subdivision. The approach used in this research is qualitative with descriptive explanative type and analysis using the theory of organization al technology from Arnold Pacey, who explained as a form of practice (physical technology) and culture (non-physical technology). HMI Denpasar Subdivision has implemented the use of organizational technology and has similarities and also differences with the use of organizational technology in the HMI Java Island Subdivision, especially in the culture of the organization (non-physical technology) because it is true that cultures between regions in Indonesia differ, which in turn makes the organizational culture also different.  Keywords ; Organizational Technology, practice and culture, physical and non-physical, Himpunan Mahasiswa Islam (HMI).